2, 3, 7, 8-Tetrachlorodibenzo-p-dioxin (TCDD) Disrupts Control of Cell Proliferation and Apoptosis in a Human Model of Adult Liver Progenitors. (19th September 2019) - Svobodová, Jana; Procházková, Jiřina; Kabátková, Markéta; Krkoška, Martin; Šmerdová, Lenka; Líbalová, Helena; Topinka, Jan; Kléma, Jiří; Kozubík, Alois; Machala, Miroslav; Vondráček, Jan
Abstract: The aryl hydrocarbon receptor (AhR) activation has been shown to alter proliferation, apoptosis, or differentiation of adult rat liver progenitors. Here, we investigated the impact of 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD)-mediated AhR activation on a human model of bipotent liver progenitors, undifferentiated HepaRG cells. We used both intact undifferentiated HepaRG cells, and the cells with silenced Hippo pathway effectors, yes-associated protein 1 (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ), which play key role(s) in tissue-specific progenitor cell self-renewal and expansion, such as in liver, cardiac, or respiratory progenitors. TCDD induced cell proliferation in confluent undifferentiated HepaRG cells; however, following YAP, and, in particular, double YAP/TAZ knockdown, TCDD promoted induction of apoptosis. These results suggested that, unlike in mature hepatocytes, or hepatocyte-like cells, activation of the AhR may sensitize undifferentiated HepaRG cells to apoptotic stimuli. Induction of apoptosis in cells with silenced YAP/TAZ was associated with upregulation of death ligand TRAIL, and seemed to involve both extrinsic and mitochondrial apoptosis pathways. Global gene expression analysis further suggested that TCDD significantly altered expression of constituents and/or transcriptional targets of signaling pathways participating in control of expansion or differentiation of liver progenitors, including EGFR, Wnt/β-catenin, or tumor growth factor-β signaling pathways. TCDD significantly upregulated cytosolic proapoptotic protein BMF (Bcl-2 modifying factor) in HepaRG cells, which could be linked with an enhanced sensitivity of TCDD-treated cells to apoptosis. Our results suggest that, in addition to promotion of cell proliferation and alteration of signaling pathways controlling expansion of human adult liver progenitors, AhR ligands may also sensitize human liver progenitor cells to apoptosis.